Effect on total microbial load and community composition with two vs six‐week topical Cadexomer Iodine for treating chronic biofilm infections in diabetic foot ulcers. Issue 6 (5th September 2019) - Malone, Matthew; Schwarzer, Saskia; Radzieta, Michael; Jeffries, Thomas; Walsh, Annie; Dickson, Hugh G.; Micali, Grace; Jensen, Slade O.
Abstract: This study compares two vs six weeks of topical antimicrobial therapy with Cadexomer Iodine in patients with diabetic foot ulcers (DFUs) complicated by chronic biofilm infections. Patients with non‐healing DFUs with suspected chronic biofilm infections were eligible for enrolment. Patients were randomised to receive either two or six weeks of treatment with topical Cadexomer Iodine. Tissue biopsies from the ulcers were obtained pre‐and‐post treatment and underwent DNA sequencing and real‐time quantitative polymerase chain reaction (PCR) to determine the total microbial load, community composition, and diversity of bacteria. Scanning electron microscopy confirmed biofilm in all 18 ulcers with suspected chronic biofilm infections. Cadexomer Iodine resulted in 14 of 18 (78%) samples achieving a mean 0.5 log10 reduction in microbial load. Regardless of treatment duration, there was no statistical difference in the reduction of total microbial loads. No difference in the rate of wound healing in the two groups was seen at 6 weeks. Cadexomer Iodine reduces the total microbial load in DFUs with chronic biofilm infections and affects microbial community composition and diversity. All ulcers in both groups showed an initial reduction in wound size with application of Cadexomer Iodine, which might reflect its effect on biofilms.